2010
DOI: 10.1089/thy.2009.0257
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes During Goiter Induction by Methylmercaptoimidazol and Inhibition by δ-Iodolactone in Rat

Abstract: The goiter inhibitory action of IL-delta is due to the inhibition of cell proliferation and the transient stimulation of apoptosis. This latter action does not involve oxidative stress. TGF-beta1 does not play a role in the autoregulatory pathway mediated by IL-delta. Iodide stimulates TGF-beta3 without the need of being organified. These results suggest that there may be more than one pathway involved in the autoregulatory mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Some studies have shown increases in peroxide content, lipid peroxidation, and the activity of the antioxidant enzyme catalase and GPx during goitrogenesis in rats , Thomasz et al 2010. The source of ROS during goitrogenesis has not been demonstrated, but NOX4 is a good candidate, according to recent findings.…”
Section: Ros and Thyroid Pathophysiologymentioning
confidence: 99%
“…Some studies have shown increases in peroxide content, lipid peroxidation, and the activity of the antioxidant enzyme catalase and GPx during goitrogenesis in rats , Thomasz et al 2010. The source of ROS during goitrogenesis has not been demonstrated, but NOX4 is a good candidate, according to recent findings.…”
Section: Ros and Thyroid Pathophysiologymentioning
confidence: 99%
“…Moreover since excess iodine increases TGF-β1 mRNA expression in sheep thyroid cells [43] and its protein synthesis in porcine thyroid cells cultured in monolayer [41], as it was mentioned, it was expected that iodolactone could also induce TGF-β1 biosynthesis. However in porcine follicles [45] and in in vivo studies in rats IL-δ did not regulate TGF-β1 synthesis, while KI increased its expression [61].…”
Section: Iodolactonementioning
confidence: 83%
“…17 Research shows that measurable concentrations of δ-iodolactone are found in the thyroid tissue, prevent excess iodide uptake and the generation of H 2 O 2 by NADPH oxidase, and regulate thyroid function. 18 Furthermore, specific iodolactones are able to inhibit signal transduction pathways to regulate cellular proliferation, modulate goiter formation, and normalize thyroid size. 14,[17][18][19][20] However, in iodine deficiency, iodolactones are obsolete, and the thyroid gland is susceptible to oxidative damage and loss of cellcycle control.…”
Section: Iodine Metabolism and Regulatory Mechanismsmentioning
confidence: 99%
“…As iodine concentrations decrease, the pituitary gland secretes thyroid-stimulating hormone (TSH) to induce NIS expression. 18…”
Section: Loss Of Autoregulation During Iodine Deficiencymentioning
confidence: 99%
See 1 more Smart Citation